A Proliferation Assessment of Third Generation Laser Uranium Enrichment Technology. Issue 2 (3rd May 2016) - Snyder, Ryan
ABSTRACT: Long-standing efforts to develop a commercially viable laser-based process for uranium enrichment, initially with atomic and later molecular isotope separation, have had limited success. This article discusses a model for a third generation of laser enrichment technology where CO2 laser light is Raman scattered to generate 16 μm photons that excite a vibrational mode in uranium-235 hexafluoride molecules within an adiabatically expanding free carrier gas jet, allowing for the partial separation of uranium isotopes by condensation repression. The SILEX (Separation of Isotopes by Laser Excitation) process being developed as part of the Global Laser Enrichment project may be one example of this separation technique. An ideal, asymmetric cascade for enriching uranium to weapon-grade levels is presented, and an analysis of the minimum laser performance requirements is included. Optimal running parameters, physical space constraints, and energy efficiency estimates are discussed. An assessment of the technical skills required is also provided. Finally, material available in an online supplement discusses possible lasers that may be utilized in such a process, and offers an introduction to dimer formation, a laser-based enrichment cascade, and a model for estimating the enrichment factor.